A Rat Model of Prenatal Zika Virus Infection and Associated Long-Term Outcomes - Morgan L. Sherer; Elise A. Lemanski; Rita T. Patel; Shannon R. Wheeler; Mark S. Parcells; Jaclyn M. Schwarz (Viruses, 2021)
Zika virus (ZIKV) is a mosquito-borne flavivirus that became widely recognized due to the epidemic in Brazil in 2015. Since then, there has been nearly a 20-fold increase in the incidence of microcephaly and birth defects seen among women giving birth in Brazil, leading the Centers for Disease Control and Prevention (CDC) to officially declare a causal link between prenatal ZIKV infection and the serious brain abnormalities seen in affected infants. Here, we used a unique rat model of prenatal ZIKV infection to study three possible long-term outcomes of congenital ZIKV infection: (1) behavior, (2) cell proliferation, survival, and differentiation in the brain, and (3) immune responses later in life. Adult offspring that were prenatally infected with ZIKV exhibited motor deficits in a sex-specific manner, and failed to mount a normal interferon response to a viral immune challenge later in life. Despite undetectable levels of ZIKV in the brain and serum in these offspring at P2, P24, or P60, these results suggest that prenatal exposure to ZIKV results in lasting consequences that could significantly impact the health of the offspring. To help individuals already exposed to ZIKV, as well as be prepared for future outbreaks, we need to understand the full spectrum of neurological and immunological consequences that could arise following prenatal ZIKV infection.